(untitled) (Modern education and development, 2025)
Literary translation plays a crucial role in promoting cross-cultural understanding. However, preserving the cultural identity of the source text poses significant challenges. Translators often face difficulties in conveying culturally specific elements, such as idioms, metaphors, traditions, and historical contexts, without distorting the original meaning. This paper explores the main challenges of preserving cultural identity in literary translation, analyzes different translation strategies, and highlights the delicate balance between linguistic accuracy and cultural authenticity.